Legal Problems Related to Exhaustion of Administrative Remedies in Administrative Procedure Act, B.E. 2539 - Pattanapaisanchai, Narut (Nitipat NIDA Law Journal, 2021)
This paper analyzes legal issues surrounding appeals of administrative orders according to the Administrative Procedure Act B.E. 2539 (1996, The Act) for which specific legal procedures are lacking, and requiring appeal within administrative departments. The research began by elucidating the fundamental concept of appeals from administrative orders and procedures for appeals from administrative orders in Thailand on legal bases. Data was gathered from legal articles and related academic research papers to analyze overall procedural issues in appealing administrative orders. Results were that problems in processing appeals include processing appeals within administrative departments by ministerial regulations through The Act reveal inherent legislative inconsistencies with the nature of appeals, as formulated in The Act. Determining conditions preceding administrative court prosecutions affects access to justice, without which administrations may not be examined by the court. In this way, the rights and freedoms of recipients of administrative orders may go unprotected. This includes setting an unreasonable period for submitting an appeal within the administrative department for those receiving an administrative order who may not have the necessary legal expertise and access to information. Protection of the parties while the appeal is considered, for example suspending administrative enforcement, is the discretion of the administrative order officer. And the period of consideration for an undetermined administrative appeal after the period stipulated by law will have further effect, resulted in the bringing plaintiff cases to the next levels of administrative courts as well. These findings indicate that issues occurring in Thailand may respond to analysis of appropriate solutions and problem- solving by repealing provisions in ministerial regulations from The Act and amending certain provisions, including the period for filing an appeal against an administrative order and determining results upon expiration of the period for considering the appeal. In addition, conditions for determining relief of enforcement of administrative orders may be reformed to assist recipients of administrative orders, affording them further protection by insuring that they are well informed, and their rights and freedoms more efficiently protected, with enabled access to justice and the administrative appeals process.